Cost effectiveness of human papillomavirus test of cure after treatment for cervical intraepithelial neoplasia in England: economic analysis from NHS Sentinel Sites Study. (1st November 2012) - Legood, Rosa; Smith, Megan; Lew, Jie-Bin; Walker, Robert; Moss, Sue; Kitchener, Henry; Patnick, Julietta; Canfell, Karen
Abstract : Objectives To evaluate the cost effectiveness of human papillomavirus testing after treatment for cervical intraepithelial neoplasia (CIN). Design Economic analysis using a Markov modelling approach to combine cost and epidemiological data from the NHS Sentinel Sites Study with data from previous studies of post-treatment recurrence rates. Setting English NHS Cervical Cancer Screening Programme. Interventions Management guidelines after treatment of CIN involving annual cytology follow-up for 10 years, compared with alternative protocols using the human papillomavirus test to reduce the amount of post-treatment surveillance. Main outcome measures Cases of underlying CIN3+ averted at 10 years and costs per 1000 women treated. Results Model predictions indicated that, at observed levels of compliance with post-treatment recommendations, management with only cytological follow-up would result in 29 residual cases of recurrent CIN3+ by 10 years and would cost £358 222 (€440 426; $574 910) (discounted) per 1000 women treated. Implementation of human papillomavirus test of cure in cytologically negative women according to the sentinel sites protocol would avert an additional 8.4 cases of CIN 3+ and reduce costs by £9388 per 1000 women treated. Conclusions Human papillomavirus test of cure would be more effective and would be cost saving compared with cytology only follow-up. The results of this evaluation support the full scale implementation of human papillomavirus test of cure after treatment of CIN within the NHS Cervical Screening Programme.